Digital Transformation Model in Empowering Seaweed Farmers: A Multi-Site Study in South Sulawesi Production Centers - Fitriani Fitriani (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to analyze the digital transformation model in empowering seaweed farmers in South Sulawesi's production centers, with a focus on its impact on increasing productivity, market access, and farmer welfare. This study uses a descriptive-qualitative approach with Jeneponto Regency as the main seaweed production area. Data collection was conducted through in-depth interviews, participant observation, and document analysis. The results show that the application of digital technologies, such as e-commerce platforms, farm management applications, and the use of social media for marketing, has a significant impact on expanding market networks and increasing production efficiency. However, the main challenges faced include limited digital literacy of farmers and access to technological infrastructure. This study recommends strengthening digital training programs, collaboration with the government and the private sector, and the development of locally based applications that suit the needs of seaweed farmers. With the implementation of the right digital transformation model, empowering seaweed farmers can encourage local economic growth and support sustainable development in coastal areas.